Kit-dependent discrepancy in D16S539 and general considerations for database matches - Zajac, Barbara Karolina; Zehner, Richard; Scheiper, Stefanie; Weissenberger, Melanie (Forensic science international. Genetics, 2018)
Throughout the last decade more companies have been offering multiplex PCR kits for forensic STR typing. As a consequence, it has been demonstrated, that an observed genotype may unexpectedly vary at a single locus when different STR kits have been used. Analysing STR profiles which have to be entered in a national database, unknown or undetected primer binding site mutations, insertions or deletions within the flanking region of STR loci may hinder matches and therefore have far-reaching consequences. The current study is a further example indicating that sequence variations in flanking regions are a common problem within STR typing which should not be underestimated. A deletion of 16 nucleotides close to the primer binding site downstream of the repeat sequence resulted in deviant genotypes at the D16S539 locus according to different STR kits used.
Gesehen am 11.03.2020